2022
DOI: 10.20944/preprints202212.0359.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial Distribution and Clustering of Drug-Resistant <em>Mycobacterium Tuberculosis</em> Infections in Rural Eastern Cape Province of South Africa

Abstract: Tuberculosis (TB), an infectious airborne disease caused by Mycobacterium tuberculosis (Mtb), is a serious public health threat reported as the leading cause of morbidity and mortality worldwide. South Africa is a high TB burden country with TB being the highest infectious disease killer. The study investigated the distribution and clustering of Mtb mutations and spoligotypes in rural Eastern Cape Province. The Mtb isolates included were 1,157 from DR-TB patients and analysed by LPA followed by spoligotyping o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 42 publications
(47 reference statements)
0
0
0
Order By: Relevance
“…The most common mutation in this gene was inhA C-15T seen in 32% and 11.6% of INH-monoresistant and MDR strains respectively. The frequency of the inhA promoter mutation observed in our study is consistent with those found in other studies in South Africa including KwaZulu-Natal (27.5%) [31], the Free State (13.4%) [24] and Eastern Cape (31.2%) [17]. In addition, the result of this study was in concordance with those reported in India (29%) [26], Ghana (11.8%) [14], and Uganda (20%) [25].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The most common mutation in this gene was inhA C-15T seen in 32% and 11.6% of INH-monoresistant and MDR strains respectively. The frequency of the inhA promoter mutation observed in our study is consistent with those found in other studies in South Africa including KwaZulu-Natal (27.5%) [31], the Free State (13.4%) [24] and Eastern Cape (31.2%) [17]. In addition, the result of this study was in concordance with those reported in India (29%) [26], Ghana (11.8%) [14], and Uganda (20%) [25].…”
Section: Discussionsupporting
confidence: 92%
“…and 95.8% [29]. A more recent systematic review reported the frequency of katG S315T mutation to be 94.9% in Sub-Saharan Africa, 64% in West Africa, 29.3% in Southeast Asia, and 38% in the United States [17]. However, a much lower frequency (23.7%) was documented by Rostamian et al [30].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations